Implementasi Undang-Undang Republik Indonesia Nomor 24 Tahun 2011 Tentang Badan Penyelenggara Jaminan Sosial pada Pasien Rawat Inap di Rumah Sakit Bhayangkara Palembang - Yofitri Heny Wahyuli (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2021)
The implementation of social security is regulated in Law Number 24 of 2011 on Healthcare and Social Security Agency (hereinafter abbreviated BPJS). Although it has been implemented quite well, there are still things that have not been done optimally. This study aims to determine how the implementation of Law Number 24 of 2011 at Bhayangkara Hospital, Palembang. This research method is qualitative, primary data were collected through observation and interviews. Parameters measured based on the policy implementation model developed by Edward III include communication, resources, disposition, and organizational structure. The results showed that the communication was good, both from the socialization and the existence of supporting tools for notification posters related to BPJS. Resources include friendly employee attitudes and courtesy, the services provided are satisfying and the flow is easy to follow. In the aspect of disposition, all implementers at Bhayangkara Hospital are honest, committed, and democratic. Some of the problems that exist are the lack of human resources at Bhayangkara Hospital compared to the number of patients, lack of medical equipment, the BPJS claim process is still inefficient, and the existence of arrears in payments from the BPJS.